Liver transplantation for erythropoietic protoporphyria in Europe - Wahlin, Staffan; Stal, Per; Adam, Rene; Karam, Vincent; Porte, Robert; Seehofer, Daniel; Gunson, Bridget K.; Hillingsø, Jens; Klempnauer, Jürgen L.; Schmidt, Jan; Alexander, Graeme; O'Grady, John; et al. (Liver transplantation, 2011)
Liver transplantation is an established lifesaving treatment for patients with severe protoporphyric liver disease, but disease recurrence in the graft occurs for the majority of recipients. Severe burn injuries may occur when protective light filters are not used with surgical luminaires. Motor neuropathy with an unclear pathogenesis is a frequent complication. We retrospectively studied 35 transplants performed for protoporphyric liver disease in 31 European patients between 1983 and 2008. Most of the patients were male (61.3%), and the mean age at the time of primary transplantation was 39 years (range = 9-60 years). The overall patient survival rates were 77% at 1 year and 66% at 5 and 10 years. The overall rate of disease recurrence in the graft was 69%. Forty-three percent of the patients experienced recurrence within a year, but this was often a transient finding that was associated with other graft complications. Phototoxic injuries due to surgical luminaires were seen in 25.0% of the patients who were not protected by filters, but these injuries were not seen in the 9 patients who were protected by filters. Significant motor neuropathies requiring prolonged ventilation complicated the postoperative course for 5 of the 31 patients (16.1%). Hematopoietic stem cell transplantation was performed for 3 patients to prevent graft loss due to disease recurrence. Prognostic markers are needed to identify patients prone to severe protoporphyric liver disease so that curative stem cell transplantation can be offered to select patients instead of liver transplantation. Liver Transpl 17:1021-1026, 2011. © 2011 AASLD.
Gesehen am 04.11.2022